Clays and Clay Minerals, Vol. 60, No. 6, 633–654, 2012. - Baioumy, Hassan M.; Gilg, H. Albert; Taubald, Heinrich (The Clay Minerals Society, 2012)
Mineralogical and geochemical variations among the Carboniferous and Cretaceous sedimentary kaolin deposits from Sinai provided an opportunity to examine the effect of the source area on compositions of the deposits. The Carboniferous kaolin deposits are mineralogically and geochemically heterogeneous. The Khaboba and Hasbar deposits consist of kaolinite, quartz, anatase, illite, chlorite, zircon, and leucoxene. The shale-normalized rare earth element (REE) patterns of the Khaboba deposit showed a slight LREE over HREE enrichment ((La/Yb)SN = 1.19-1.51) with a MREE depletion (Gd/ Gd*SN = 0.51-0.75), while the Hasbar kaolin had a MREE enrichment. The Abu Natash kaolin deposit consisted of kaolinite, anatase, and a little quartz with larger TiO2, Cr, and V and smaller Zr and Nb contents compared to other Carboniferous deposits. The shale-normalized REE patterns of the Abu Natash deposit exhibited a positive Eu anomaly (Eu/Eu*SN = 1.28-1.40) and a MREE enrichment (Gd/Gd*SN = 1.41-2.05). The Cretaceous deposits were relatively homogeneous in terms of mineralogical composition and geochemistry and are composed of kaolinite, quartz, anatase, rutile, zircon, and leucoxene. The Cretaceous kaolin deposits showed mostly flat shale-normalized REE patterns with a variable LREE depletion. The presence of illite and chlorite, the absence of rutile, large Zr and Nb contents, and the REE patterns suggested a component of weathered low-grade metasediments as a source for the Carboniferous deposits in the Khaboba and Hasbar areas, while the large Ti, Cr, and V, and small quartz contents indicated mafic source rocks for the Abu Natash deposit. The abundance of high-Cr rutile and the absence of illite and chlorite, and large Zr, Ti, Cr, and V contents suggested a mixture of medium- to high-grade metamafic and granitic rocks as source rocks for the Cretaceous kaolin deposits. The occurrence of alkaline rocks in the source of the deposits studied was identified by high-Nb contents and the presence of bastnaesite. The mineralogical and geochemical heterogeneity and lesser maturity of the Carboniferous deposits suggested local sources for each deposit and their deposition in basins close to the sources. The mineralogical and geochemical homogeneity and maturity of the Cretaceous deposits, on the other hand, indicated common sources for all deposits and their deposition in relatively remote basins.
Mineralogy And Geochemistry Of The Sedimentary Kaolin Deposits From Sinai, Egypt: Implications For Control By The Source Rocks
gsccm60608-bai.pdf -- 6,480 KB
Keywords: Periodicals; Geology; Egypt; Geochemistry; Mineralogy; Origin; Sedimentary Kaolin Deposits; Sinai; Source